Sosialisasi Upaya Pencegahan Perilaku Bullying Pada Siswa SMPN Di Tirtajaya - Ajat Sudrajat (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this service is to socialize as an effort to prevent bullying practices at one of the SMPN in Tirtajaya, Karawang. The dedication method used is a qualitative descriptive study involving teachers and students from SMPN Karawang as participants. Data was collected through class observation and analysis of documents related to the outreach program. The results showed that the bullying prevention outreach program had been well implemented at the Karawang Junior High School and had achieved several important goals. In the implementation process, several challenges were encountered, such as differences in students' understanding and awareness of the issue of bullying. However, awareness about the importance of stopping bullying behavior and creating a safe and inclusive school environment is gradually increasing. This research provides valuable insights for the development of more effective outreach programs to address the problem of bullying in other schools.